Modified phenolic resins for manufacturing composite products

By adding 2-30% solid adsorbents, such as zeolite, to phenolic resins, the voids and defects caused by volatile emissions during the curing process of phenolic resins is solved, and the significant reduction in ammonia production and improvement in production efficiency is achieved.

JP2025509349APending Publication Date: 2025-04-11BAKELITE UK HLDG LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024553578
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-09
Filing Date
2023-03-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When using phenolic resins, there are voids and defect problems caused by volatile emissions, and these volatile emissions cause corrosion and interference to equipment and molds, increasing production cycle and energy consumption.

Method used

Add 2-30% solid adsorbents, such as zeolite, to the phenol-aldehyde novolac resin, to absorb the generated ammonia, thereby reducing volatile emissions.

Benefits of technology

By increasing the solid adsorbent, the amount of ammonia generated is significantly reduced, with a decrease of more than 21%, avoiding the generation of voids and defects, while reducing corrosion to equipment and molds, improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509349000016
    Figure 2025509349000016
  • Figure 2025509349000017
    Figure 2025509349000017
  • Figure 2025509349000001
    Figure 2025509349000001
Patent Text Reader

Abstract

A binder composition and method for making the same. The binder composition can include 50-93 wt. % phenolic-aldehyde novolac resin, 5-15 wt. % hexamine, 0-10 wt. % other additives, and 2-30 wt. % at least one sorbent, based on the total weight of the resin. The binder composition is particularly useful for wood products.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 318,061, filed March 9, 2022, the entirety of which is incorporated herein by reference.

[0002] FIELD OF THE DISCLOSURE Embodiments of the present invention relate generally to phenolic resins. [Background technology]

[0003] Phenolic resins are well-known adhesives that can be used to manufacture laminated products, molded products, among others. Phenolic resins, especially novolacs, also have a wide variety of applications as heat resistants, friction materials, abrasives, felt bonds, and curing agents for epoxies. Excellent adhesion, high heat and chemical resistance, and flame-smoke-toxicity (FST) properties are some of the properties that novolac resins offer that make them suitable for such applications.

[0004] However, a traditional problem faced by these industries is the volatile emissions generated during the curing of phenolic resins. These emissions can cause voids and defects in the final article in which the phenolic resin is the binder material. This is a major cause of scrap generation across multiple markets. These volatile emissions can also cause damage to equipment and mold surfaces, which routinely require downtime for cleaning and resurfacing due to the chemical corrosive nature of the gases produced and the interference of the released gases with other components during the formation of the molded part.

[0005] For example, novolacs are often crosslinked and are known to release ammonia gas when cured with an amine-containing hardener. For example, novolac powders containing hexamethylenetetramine ("hexamine") are widely used in wood molding applications. The novolac powder and hexamine are mixed with wood particles, pressed and cured at high temperatures to give stable molded parts that exhibit high strength, minimal water absorption, and are paintable. During the curing process, the hexamine decomposes into ammonia and formaldehyde. The formaldehyde acts to crosslink the novolac polymer into the final product, which retains its shape and exhibits chemical resistance. The ammonia is released as a gas, which is odorous and can produce toxic VOCs.

[0006] In many cases, it is necessary to post-bake the parts after curing to completely remove ammonia from the product and prevent the slow emission of undesirable odors from the final product. Such post-baking processes add additional cycle time and energy to the overall manufacturing process.

[0007] Additionally, the ammonia released from this process can have adverse effects on molding equipment. Particularly in molded wood products, the released ammonia gas can cause the molded parts to stick to the mold, requiring manual remediation to remove and clean the mold.

[0008] To avoid these harmful consequences of released ammonia, attempts have been made to reduce the amount of hexamine present in the formulation. However, this solution reduces the crosslink density of the novolac resin and therefore reduces the strength of the final product. Other attempts have been made to remove ammonia by modifying the heat treatment cycle by opening and closing the mold to release the trapped ammonia and other gases, but this effectively increases the processing time and energy to make the molded parts. Summary of the Invention [Problem to be solved by the invention]

[0009] Thus, there remains a need for improved resins and methods for using the same in the manufacture of molded composite articles. [Means for solving the problem]

[0010] Provided herein is a binder composition and a method for making the same. In at least one embodiment, the binder can include 50-93 wt. % phenolic-aldehyde novolac resin, 5-15 wt. % hexamine, 0-10 wt. % other additives, and 2-30 wt. % at least one sorbent, based on the total weight of the resin. The binder composition is particularly useful for wood products, more particularly molded wood products. [Brief description of the drawings]

[0011] In order that the above-mentioned features of the present invention may be understood in detail, the invention, briefly summarized above, can be more particularly described by reference to embodiments, some of which are illustrated in the accompanying drawings. It should be noted, however, that the accompanying drawings only illustrate typical embodiments of the present invention and therefore should not be considered as limiting its scope, as other equally effective embodiments of the present invention are also permissible.

[0012] Figure 1 shows a side view of the three plaques produced, showing imperfections due to trapped volatiles: top sample: 2854-6-1; middle sample: 2854-6-2; and bottom sample: 2854-6-3.

[0013] Figure 2 shows the visual contamination on the Q-plates after the press cycle. Top row: 2854-1-1, 2854-1-2-1 and 2854-1-3-1. Bottom row: 2854-1-4-1, 2854-1-5-1 and 2854-1-6-1. Note: The "B" on each plate indicates the bottom plate used for testing and evaluation of contamination.

[0014] Detailed Description It has been surprisingly and unexpectedly discovered that the addition of zeolite or other suitable solid sorbent to a phenol-aldehyde-hexamine resin composition results in a significant reduction (i.e., greater than 21%) in the ammonia produced during the resin curing process without reducing the amount of hexamine in the resin.

[0015] The resins can be produced by any suitable process. For example, one or more phenolic compounds, one or more aldehyde compounds, and optionally one or more catalysts can be conducted, charged, or otherwise introduced into a reaction vessel to provide a reaction mixture therein. The reaction mixture can be agitated. For example, if a solvent is also present in the reaction vessel, the reaction mixture can be agitated to improve and / or maintain a uniform or substantially uniform distribution of the reactants in the solvent, or a uniform or substantially uniform distribution of the solvent in the reaction mixture. The components of the reaction mixture can be combined in one or more mixers. A mixer can be or include any device, apparatus, or combination of device(s) and / or apparatus(es) capable of batch, intermittent, and / or continuous mixing, blending, contacting, or otherwise combining two or more components. Exemplary mixers include, but are not limited to, mechanical mixer agitation, ejectors, static mixers, mechanical / power mixers, shear mixers, ultrasonic mixers, vibration mixing, such as moving the mixer itself, or any mixture thereof. The mixer may include one or more heating jackets, heating coils, internal heating elements, cooling jackets, cooling coils, internal cooling elements, etc., to regulate the temperature therein. The mixer may be an open or closed vessel. The components of the reaction mixture may be combined in the mixer under vacuum, at atmospheric pressure, or at pressures greater than atmospheric pressure. The sorbent may be added to the phenol-aldehyde composition before or after the addition of hexamine.

[0016] The phenolic resin can have a molar ratio of aldehyde component(s) or compound(s) to phenolic component(s) or compound of less than 1:1. For example, the molar ratio of aldehyde component(s) or compound(s) to phenolic component(s) or compound can be about 0.2:1, about 0.3:1, about 0.4:1, about 0.5:1, about 0.6:1, about 0.7:1, about 0.8:1, or about 0.9:1. The phenolic resin can also have a molar ratio of aldehyde to phenols of about 0.5:1 to about 0.95:1. The molar ratio of aldehyde to phenols can also range from a low of about 0.2:1, about 0.3:1, or about 0.4:1 to a high of about 0.7:1, about 0.8:1, or about 0.95:1.

[0017] The one or more catalysts can include, but are not limited to, one or more acid catalysts. Suitable acid catalysts include hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, sulfonic acid, sulfamic acid, haloacetic acid, and combinations thereof.

[0018] The reaction mixture can have a catalyst concentration ranging from a low of about 0.2% by weight, about 1% by weight, to a high of about 7% by weight, about 12% by weight, or about 20% by weight, based on the combined weight of the phenol, formaldehyde, and catalyst. For example, the reaction mixture can have a catalyst concentration of about 0.2% by weight to about 1% by weight, about 1% by weight to about 5% by weight, about 5% by weight to about 10% by weight, about 8% by weight to about 15% by weight, or about 12% by weight to about 20% by weight, based on the combined weight of the phenol, formaldehyde, and catalyst. In another example, at least about 0.001 moles of catalyst per mole of phenolic component can be used. In another example, the reaction mixture can have a catalyst concentration of about 0.02 moles to about 1 mole per mole of phenolic component. The catalyst can be added all at once to the reaction mixture initially, or the catalyst can be added stepwise in two or more additions, or continuously over time.

[0019] In the presence of one or more acid catalysts, one or more phenolic components and one or more aldehyde components can be reacted at a temperature of about 20°C, about 25°C, about 30°C, about 35°C, or about 40°C to about 50°C, about 55°C, about 60°C, about 65°C, about 70°C, about 75°C, about 80°C, about 85°C, about 90°C, about 95°C, or about 100°C, or about 105°C.

[0020] The phenolic component can include one or more phenolic compounds. The one or more phenolic compounds can be monohydroxyaromatic and / or dihydroxyaromatic compounds. For example, the phenolic compound can be phenol, one or more substituted phenolic compounds, one or more unsubstituted phenolic compounds, or any combination or mixture of substituted and / or unsubstituted phenolic compounds. For example, the phenolic component can be or include phenol itself (monohydroxybenzene). Exemplary substituted phenolic compounds include, but are not limited to, alkyl-substituted phenols such as cresols, xylenols, and other substituted monohydroxybenzene compounds; cycloalkyl-substituted phenols such as cyclohexylphenol; alkenyl-substituted phenols; aryl-substituted phenols such as p-phenylphenol; alkoxy-substituted phenols such as 3,5-dimethyloxyphenol; aryloxyphenols such as p-phenoxyphenol; and halogen-substituted phenols such as p-chlorophenol. Dihydric phenols or dihydroxyaromatic compounds such as catechol, resorcinol, hydroquinone, bisphenol A, and bisphenol F can also be used. For example, the phenolic component can be or can include, but is not limited to, resorcinol, phenol, catechol, hydroquinone, naphthol, pyrogallol, 5-methylresorcinol, 5-ethylresorcinol, 5-propylresorcinol, 4-methylresorcinol, 4-ethylresorcinol, 4-propylresorcinol, resorcinol monobenzoate, resorcinol monosinate, resorcinol diphenyl ether, resorcinol monomethyl ether, resorcinol monoacetate, resorcinol dimethyl ether, phloroglucinol, benzoylresorcinol, resorcinol rosinate, alkyl substituted resorcinols, aralkyl substituted resorcinols, 2-methylresorcinol, phloroglucinol, 1,2,4-benzenetriol, 3,5-Dihydroxybenzaldehyde, 2,4-dihydroxybenzaldehyde, 4-ethylresorcinol, 2,5-dimethylresorcinol, 5-methylbenzene-1,2,3-triol, 3,5-dihydroxybenzyl alcohol, 2,4,6-trihydroxytoluene, 4-chlororesorcinol, 2',6'-dihydroxyacetophenone, 2',4'-dihydroxyacetophenone, 3',5'-dihydroxyacetophenone, 2,4,5-trihydroxybenzaldehyde, 2,3,4-trihydroxybenzaldehyde, 2,4,6-trihydroxybenzaldehyde, 3,5-dihydroxybenzoic acid, 2,4-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 1,3-dihydroxy xynaphthalene, 2',4'-dihydroxypropiophenone, 2',4'-dihydroxy-6'-methylacetophenone, 1-(2,6-dihydroxy-3-methylphenyl)ethanone, 3-methyl 3,5-dihydroxybenzoate, methyl 2,4-dihydroxybenzoate, galacetophenone, 2,4-dihydroxy-3-methylbenzoic acid, 2,6-dihydroxy-4-methylbenzoic acid, methyl 2,6-dihydroxybenzoate, 2-methyl-4-nitroresorcinol, 2,4,5-trihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid, 2,3,4-trihydroxybenzoic acid, 2,4,6-trihydroxybenzoic acid, 2-nitrophloroglucinol, or any mixture thereof. The phenolic component may include any combination of two or more phenolic compounds combined with each other and / or added to the reaction mixture independently of each other.

[0021] The aldehyde component may include one or more aldehyde compounds. The aldehyde compound may be or may include one or more substituted aldehyde compounds, one or more unsubstituted aldehyde compounds, or any mixture of substituted and / or unsubstituted aldehyde compounds. Suitable aldehyde compounds include, but are not limited to, aldehydes having the formula R'CHO, where R' is hydrogen or a hydrocarbyl group. Suitable hydrocarbyl groups may include 1 to 8 carbon atoms. Suitable aldehyde compounds may also include so-called masked aldehydes or aldehyde equivalents, such as acetals or hemiacetals. Exemplary aldehyde compounds may be, but are not limited to, formaldehyde, paraformaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, furfuraldehyde, benzaldehyde, or any mixture thereof. Yet another suitable formaldehyde compound can be formaldehyde present in a prepolymer or precondensate, such as a urea-formaldehyde precondensate (UFC).

[0022] It will be understood by those skilled in the art that the term "aldehyde" in the above context of the condensation of a hydroxyaromatic monomer with an aldehyde can further include an aldehyde precursor, also referred to as an aldehyde source or donor, i.e., a compound capable of generating an aldehyde under the conditions used, or capable of providing substantially the same reactive radical expected from the condensation of a hydroxyaromatic monomer with the corresponding aldehyde. Suitable aldehyde precursors include, but are not limited to, compounds such as formalin, para-formaldehyde ("paraform"), α-polyoxymethylene, hexamethylenetetramine ("hexamine"), oxazolidines, 1,3,5-trioxacyclohexane, and the like.

[0023] The aldehyde compound can also be or include, but is not limited to, one or more polyfunctional aldehyde compounds. As used herein, the terms "polyfunctional aldehyde compound" and "polyfunctional aldehyde" are used interchangeably and refer to a compound having at least two functional groups, at least one of which is an aldehyde group. For example, a polyfunctional aldehyde can include two or more aldehyde functional groups. In another example, a polyfunctional aldehyde can include at least one aldehyde functional group and at least one functional group other than an aldehyde functional group. As used herein, the term "functional group" refers to a reactive group in a polyfunctional aldehyde compound, including, but not limited to, an aldehyde group, a carboxylic acid group, an ester group, an amide group, an imine group, an epoxide group, an aziridine group, an azetidinium group, and a hydroxyl group.

[0024] The polyfunctional aldehyde compound may contain two or more carbon atoms and may have two or more aldehyde functional groups. For example, the polyfunctional aldehyde compound may contain 2, 3, 4, 5, 6 or more carbon atoms and may have two or more aldehyde functional groups. The polyfunctional aldehyde compound may contain two or more carbon atoms and may have at least one aldehyde functional group and at least one functional group other than the aldehyde group, such as a carboxylic acid group, an ester group, an amide group, an imine group, an epoxide group, an aziridine group, an azetidinium group, and / or a hydroxyl group. For example, the polyfunctional aldehyde compound may contain 2, 3, 4, 5, 6 or more carbon atoms and may have at least one aldehyde functional group and at least one functional group other than the aldehyde group, such as a carboxylic acid group, an ester group, an amide group, an imine group, an epoxide group, an aziridine group, an azetidinium group, and / or a hydroxyl group.

[0025] Suitable bifunctional or difunctional aldehyde compounds containing three or more carbon atoms and having two aldehyde functional groups (-CHO) can be represented by the following chemical formula:

[0026] [ka] wherein R can be a divalent aliphatic, alicyclic, aromatic or heterocyclic group having 1 carbon atom to 12 carbon atoms. Exemplary polyfunctional aldehydes include, but are not limited to, malondialdehyde, succindialdehyde, glutaraldehyde, 2-hydroxyglutaraldehyde, β-methylglutaraldehyde, adipaldehyde, pimelaldehyde, suberaldehyde, malealdehyde, fumaraldehyde, sebacaldehyde, phthalaldehyde, isophthalaldehyde, terephthalaldehyde, ring-substituted aromatic aldehydes, or any combination or mixture thereof. A suitable bifunctional or difunctional aldehyde containing two carbon atoms and having two aldehyde functional groups is glyoxal.

[0027] Exemplary polyfunctional aldehyde compounds containing aldehyde groups and functional groups other than aldehyde groups may include, but are not limited to, glyoxylic acid, glyoxylic acid esters, glyoxylic acid amides, 5-(hydroxymethyl)furfural, or any combination or mixture thereof. The aldehyde groups in the polyfunctional aldehyde compounds may exist in other forms, for example, as hydrates. Thus, any form or derivative of a particular polyfunctional aldehyde compound may be used to prepare the resin compositions discussed and described herein. For example, in the context of glyoxylic acid, glyoxylic acid, glyoxylic acid monohydrate, and / or glyoxylate may be used to prepare a phenolic resin.

[0028] When the aldehyde component is formaldehyde, a formaldehyde scavenger can be used to reduce the amount of free formaldehyde in the resin. Exemplary formaldehyde scavengers include, but are not limited to, urea, amines, ammonia, and alkanolamines.

[0029] When the aldehyde component is formaldehyde, the phenolic resin can have an amount of free formaldehyde of about 0.001% by weight to about 6% by weight. For example, the phenolic resin can have a concentration of free formaldehyde of about 0.03% by weight to about 0.13% by weight, about 0.1% by weight, about 0.5% by weight, about 1% by weight, or about 2% by weight to about 3% by weight, about 5% by weight, or about 6% by weight, based on the total weight of the phenolic resin. In another example, the phenolic resin can have a concentration of free formaldehyde of less than 3% by weight, less than 2% by weight, less than 1% by weight, less than 0.5% by weight, less than 0.3% by weight, less than 0.2% by weight, less than 0.15% by weight, or less than 0.1% by weight, based on the total weight of the phenolic resin.

[0030] The phenolic resin can have a concentration of free phenol of about 0.1%, about 0.5%, about 1%, or about 2% to about 5%, about 10%, or about 15% by weight based on the total weight of the phenolic resin. The phenolic resin can have an amount of free phenol of about 0.1% and about 6%, about 2% and about 8%, about 5% and about 12%, or about 7% and about 15% by weight based on the total weight of the phenolic resin.

[0031] The phenolic resin has a weight average molecular weight (M) of about 200, about 300, or about 400 to about 900, about 1,500, or about 40,000. w ).

[0032] The phenolic resin has a number average molecular weight (M) of about 200, about 300, or about 400 to about 900, about 1,500, or about 40,000. n ).

[0033] The phenolic resin can have a z-average molecular weight (Mz) of about 200, about 300, or about 400 to about 900, about 1,500, or about 40,000. w , M n and M. zcan be measured using gel permeation chromatography (GPC), also known as size exclusion chromatography (SEC).

[0034] Various methods can be used to condense the hydroxyaromatic compound and aldehyde components to form a thermoplastic solid composition. The condensation of one or more hydroxyaromatic compounds, aldehydes and catalysts can be carried out by melt condensation or solution condensation. Process control, such as staged monomer addition, staged catalyst addition, pH control, amine modification, etc., is useful to maintain the properties of the resin. Exemplary methods that can be used to produce the phenolic resins described herein are further described in U.S. Pat. No. 6,706,845.

[0035] Suitable phenolic resins include, but are not limited to, phenol-formaldehyde resins, resorcinol formaldehyde resins, and phenol-resorcinol-formaldehyde resins, bisphenol A modified resins, bisphenyl F modified resins, and t-butylphenol modified resins.

[0036] Composite products can be manufactured by contacting one or more substrates with a resin composition and at least partially curing the resin composition to produce a composite product. Suitable substrates include lignocellulosic materials, such as wood products. Lignocellulosic materials are cellulosic materials and can be derived from a number of natural sources, including wood. Other suitable sources include sugarcane bagasse, straw, corn stalks, and other waste vegetable matter. In certain embodiments, the lignocellulosic materials can be derived from various types of wood in the form of wood fibers, chips, shavings, flakes, particles, veneers, and powders. The resin compositions provided herein can be used with a variety of soft and hard woods, such as, for example, Douglas Fir, White Fir, Hemlock, Larch, Southern Yellow Pine, Ponderosa Pine, Spruce, Black Pine, and combinations comprising at least one of the above. In particular, Douglas fir, ponderosa pine and southern yellow pine are useful for the resin compositions provided herein. The resin composition can be applied to wood particles by blending the particles with the resin composition while tumbling or stirring the particles in a blender or equivalent device.

[0037] One or more acids, heat, catalysts and / or pressure can be added, mixed, blended or otherwise combined or transferred to the resin composition before, during and / or after application of the resin composition to the wood particles to provide a composite. The acid, heat and / or pressure can initiate or initiate and / or accelerate the curing of the resin. In certain embodiments, one or more curing accelerators can be added to the resin composition to reduce the curing time. The amount of accelerator that can be added to the resin composition to initiate or initiate the curing of the resin composition can be about 0.01% by weight, about 0.5% by weight, about 0.8% by weight or about 1% by weight to about 5% by weight based on the combined weight of the resin composition and additives. For example, the amount of accelerator additive that can be added to the resin composition to cause or initiate curing of the resin can range from a low of about 0.1%, 0.3% or 0.5% by weight to a high of about 1.0%, 3.0% or 5.0% by weight, based on the combined weight of the resin composition and catalyst.

[0038] The wood composite may contain from about 2.0% to about 40% by weight of the resin composition, based on the total weight of the wood composite. The amount of the resin composition in the wood composite may also range from a minimum of about 2.0%, 5% or 10% by weight, to a maximum of about 20%, 30% or 40% by weight, based on the total weight of the wood composite. The amount of the resin composition in the wood composite may also range from a minimum of about 3.5%, 7.5% or 11.5% by weight, to a maximum of about 15.0%, 17.5% or 27.5% by weight, based on the total weight of the wood composite.

[0039] Suitable bases that can be used to promote curing in the resin composition include, but are not limited to, organic bases, inorganic bases, or any mixture thereof. Exemplary inorganic bases include, but are not limited to, magnesium oxide, magnesium hydroxide, calcium oxide, calcium hydroxide, lime, hexamethylenediamine, lithium hydroxide. Suitable acids that can be used to promote curing in the resin composition include, but are not limited to, adipic acid, fumaric acid, salicylic acid, and oxalic acid.

[0040] As used herein, the terms "cure," "cured," and similar terms are intended to refer to structural and / or morphological changes that occur in a resin composition as it cures, causing covalent chemical reactions (crosslinking), ionic interactions or clustering, improved adhesion to a substrate, phase transition or phase change, and / or hydrogen bonding. As used herein, the phrases "at least partially cure," "at least partially cured," and similar terms are intended to refer to a resin composition that has undergone at least some covalent chemical reactions (crosslinking), ionic interactions or clustering, improved adhesion to a substrate, phase transition or phase change, and / or hydrogen bonding, but may also undergo additional covalent chemical reactions (crosslinking), ionic interactions or clustering, improved adhesion to a substrate, phase transition or phase change, and / or hydrogen bonding.

[0041] Any suitable curing technique can be used to cure the resin composition provided herein, for example, a heat curing technique can be used in which the resin composition is heated to a temperature of about 100°C to about 200°C, more preferably about 120°C to about 180°C, for about 5 to about 120 minutes, more preferably about 30 to about 60 minutes.

[0042] Before or during the curing step, one or more suitable release agents can be added to the resin composition.Suitable release agents include, but are not limited to, calcium stearate, zinc stearate, ethylene bisstearylamide, methylenestearylamide, oxystearylamide, stearylamide, polyethylene wax, carnauba wax, montan wax, paraffin wax, polyethylene wax, silicone compound, and linoleylamide.In some embodiments, for example, the release agent can include a surfactant, such as calcium stearate.

[0043] The release agent can be present in the composition in any suitable amount.For example, in some embodiments, the release agent can be present in the composition in an amount of about 0.01% by weight to about 20% by weight, based on the total weight of the composition.In some embodiments, for example, the release agent can be present in the composition in an amount ranging from a minimum of about 0.01% by weight, 1.0% by weight, or 4.0% by weight to a maximum of about 10% by weight, 15% by weight, or 20% by weight, based on the total weight of the composition.

[0044] When the resin composition includes one or more additional additives, the amount of each additive can be from a minimum of about 0.001 wt%, about 0.01 wt%, about 0.1 wt%, about 1 wt%, or about 5 wt%, to a maximum of 20 wt%, about 30 wt%, about 40 wt%, or about 50 wt%, based on the total weight of the composition. For example, when the resin composition includes one or more additional additives, the amount of each additive can be about 0.01 wt% to about 5 wt%, about 1 wt% to about 10 wt%, about 5 wt% to about 40 wt%, about 0.01 wt% to about 50 wt%, about 2 wt% to about 20 wt%, about 15 wt% to about 45 wt%, or about 1 wt% to about 15 wt%, based on the total weight of the composition.

[0045] Despite the presence of mold release agents, when hexamine is used to make resins, the production of ammonia is expected. However, it was not expected, and only recently discovered, that ammonia would foul molding equipment used to make molded wood products containing resin compositions including those described herein. Such fouling, in turn, causes molded products to stick to their molds, which results in defects in the product, reduced runtime, and wasted downtime for additional cleaning and maintenance.

[0046] Another object of the present invention is to address the problems caused by ammonia emissions and air treatment ventilation for making composite products. The Environmental Protection Agency (EPA) has raised concerns about ammonia contamination of water and its contribution as a particulate matter precursor. Therefore, performing ventilation treatment before air release or recycling to the process places an energy burden on manufacturing. In addition to air treatment, multiple mold openings in a short period of time to release volatile materials increase the cycle time per part. The amount of ammonia released in turn reduces manufacturing efficiency through both energy consumption and cycle time.

[0047] To address these and other problems caused by the presence of ammonia, solid sorbent materials can be added to the resin precursor and / or resin product to capture the ammonia molecules formed during the resin curing process. By "solid sorbent material" is meant a diverse range of porous solid phase materials, including microporous zeolites and molecular sieves, activated carbon, and other metal-organic frameworks, that can be used to adsorb, absorb, or otherwise capture ammonia. Preferred sorbents include zeolites and molecular sieves. Zeolites include, but are not limited to, natural and synthetic hydrous aluminosilicates of alkali and alkaline earth metals. These are crystalline inorganic polymers with [SiO4] and [AlO4] tetrahedra that form a porous substrate. Examples of natural zeolites include clinoptilolite, heulandite, stilbite, natrolite, analcime, chabazite, gismondine, phillipsite, levinite, mordenite, andalusite, erionite, scolecite, ferrierite, and laumonite. Synthetic zeolites include, but are not limited to: Linde Type A (LTA), Linde Types X and Y, Silicalite-1, ZSM-5, Linde Type B, MCM-41 and other synthetic aluminosilicate molecular sieves. A preferred zeolite is clinoptilolite.

[0048] Silica gel can also be used. The sorbent should have a pore size suitable for sorbing ammonia. Ammonia has an effective radius of about 3.6 Å, therefore, a suitable sorbent should have a pore size greater than about 3.6 Å, but smaller than other components that should not be trapped (e.g., a pore size of about 4 Å).

[0049] For example, the sorbent can have an average pore size of about 2 Å to about 20 Å. In some embodiments, for example, the sorbent can have an average pore size of about 3 Å to about 10 Å, or about 3 Å to about 12 Å. In some embodiments, the sorbent can have an average pore size of about 4 Å to about 10 Å, e.g., about 4 Å to about 8 Å, or about 4 Å to about 6 Å. In some embodiments, the sorbent can have an average pore size of about 6 Å to about 10 Å. Pore size is typically measured by nitrogen adsorption at 77 K using density functional theory.

[0050] The amount of sorbent added to the reaction mixture or to the resin after condensation is important. The amount of sorbent can be about 1% to 30% by weight, based on the total weight of the phenolic component and / or the total weight of the resin composition. The amount of sorbent can also range from a minimum of about 1%, 2%, 3% or 5% by weight, based on the total weight of the phenolic component and / or the total weight of the resin composition, to a maximum of about 10%, 20% or 30% by weight. The amount of sorbent can also range from a minimum of about 1%, 2%, 3% or 5% by weight, based on the total weight of the phenolic component and / or the total weight of the resin composition, to a maximum of about 10%, 20% or 30% by weight. The weight ratio of sorbent to hexamine in the resin composition can be about 1:0.5; about 1:0.6; about 1:0.7; about 1:0.8; about 1:0.9; about 1:1; about 1:0.55; about 1:0.65; about 1:0.75; about 1:0.6; 1:0.85; or about 1:0.95.

[0051] According to the present invention, a binder composition is claimed comprising: 50-93 wt. % phenolic-aldehyde novolac resin; 5-15 wt. % hexamine; and 2-30 wt. % of at least one sorbent, based on the total weight of the resin.

[0052] Further, according to the present invention, 1. A cured resin composition comprising: 50-93 wt. % of a phenol-aldehyde novolac resin; 5-15 wt. % of hexamine; and 2-30 wt. % of at least one sorbent, based on a total weight of the resin composition; The cured resin composition is claimed to have a glass plate flow of 10 mm to 200 mm at 125°C; a modulus of rupture (MOR) of about 40 to about 150 MPa as measured by ASTM D790-03; a maximum bending stress (elastic modulus) of about 5.0 to 8.0 GPa; and a char residue percentage of about 30 to about 75% at 1,000°C in nitrogen as measured by thermogravimetric analysis (TGA).

[0053] In order to provide a better understanding of the foregoing discussion, the following non-limiting examples are provided. Although the examples may be directed to specific embodiments, they should not be construed as limiting the invention in any particular respect. Unless otherwise indicated, all parts, proportions and percentages are by weight. EXAMPLES

[0054] example A plant sample of commercial grade solid novolac-hexamine composition lot # (LK1LE7778) ("Resin 1") was modified with clinoptilolite zeolite from IdaOre or limestone (dolomitic limestone) from Old Castle Mineral CastleCarb 6 and evaluated for outgassing of ammonia. Resin 1 is a mixture of solid novolac resin and granular hexamine that has been ground in a grinder until 96.5-99.5% by volume of all particles are 74 microns or less, with hexamine being about 8% of the total weight of the composition and novolac being about 92%. To incorporate inorganic materials, such as zeolite and / or limestone, into the resin, the mixture of resin and inorganic materials was placed in a mill, milled for 10 seconds, paused for 10 seconds, milled for 10 seconds, paused for 10 seconds, tapped the top of the mill several times with the handle of a wooden spatula, milled for 10 seconds, and the sample was removed from the mill.

[0055] Table 1 shows the compositions of three samples evaluated for ammonia emissions using Modified Resin 1, and Table 2 shows the compositions of two additional samples ("Novolac 1" above) with 7.5 wt. % hexamine fixed, which were also evaluated for ammonia emissions.

[0056] [Table 1]

[0057] [Table 2]

[0058] Table 3 below shows additional sample preparations of resin powders that were prepared and tested according to the test procedures described below. For each sample, the ingredients were milled together using a mini mill to form a uniform powder. The resulting free-flowing powder was measured by Malvern particle size analysis to yield particles with greater than 98% being 74 microns or less.

[0059] In all tables provided herein, percentages are by total weight unless specifically stated otherwise.

[0060] [Table 3] Novolac 1 was an oxalic acid catalyzed resin that contained no release agent.

[0061] Novolac 2 was a sulfuric acid catalyzed resin that was neutralized after polymerization was complete. Novolac 2 contained an amount of a mold release agent.

[0062] Novolac 3 was the same resin as Novolac 2 without the release agent.

[0063] Novolac 4 was a sulfuric acid catalyzed resin that was neutralized after polymerization was complete. The formaldehyde to phenol molar ratio of this resin resulted in a cone-plate viscosity of approximately 1200 cps at 175°C with a free phenol content of approximately 4%.

[0064] Reduced outgassing Outgassing during cure was expected since the hardener, hexamine, is known to decompose and release ammonia and formaldehyde, but if there is an excess of gas or if the resin cures faster than it can release the gas, this outgassing can cause defects described as "foaming," "bubbling," or "puffiness." With the reduction of hexamine and the introduction of the selective microporous sorption material, clinoptilolite, there was significantly less visually observed outgassing during the B-stage process to make resin plaques (see procedure below) from resin samples 2854-6-1, 2854-6-2, and 2854-6-3. When plaques were made with a B-stage time of 2 minutes, the sample without clinoptilolite showed defects due to trapped volatiles, as shown in Figure 1, which shows the side view of the three plaques produced. The top sample was 2854-6-1. The middle sample was 2854-6-2. The bottom sample was 2854-6-3. The top and bottom samples (i.e., those without clinoptilolite) had imperfections due to trapped volatiles:

[0065] tube furnace A temperature profile consisting of a 10°C / min ramp to 164°C with a 30 minute soak time was used. The impinger was loaded with 150 mL of dilute methanesulfonic acid (MSA) with a constant nitrogen flow of approximately 50 mL / min. The ceramic boat was placed in a Lindberg Model 5035 tube furnace and sealed. After the temperature profile was completed, the impinger was washed with 50 mL of DI water. The impinger solution was then tested using an autotitrator.

[0066] Tube furnace sample preparation Resin samples were loaded onto 0.5 mm glass beads at 20-25% and placed in 97x16x10 mm Fisherbrand (登録商標) Samples were prepared by placing the resin in an FB-963-C ceramic boat. The sample was mixed by placing an excess of resin in a small glass sample vial along with glass beads, fitting the plastic cap tightly, and shaking thoroughly to coat the beads. 1-1.2 grams of shaken sample (resin + glass) was loaded onto the boat, where the loss of resin in the small mixing vessel was measured to obtain the amount of resin loaded onto the boat.

[0067] Automatic titrator Samples were titrated using a Metrohm Autotitrator Tiamo fitted with a dual burette (0.1N HCl and 0.1N NaOH) and the target endpoint was calculated to consume approximately 10mL of titrant. A Unitrode electrode was used to measure and determine sample endpoints. SOPs RD-016, RD-IR-384, RD-IR-385, RD-IR-391.

[0068] Impinger Solution The impinger solution was prepared using 70% MSA and water with a target concentration of 0.040% MSA. This concentration was chosen because 150 mL of solution was used in the impinger, which targets 30% capacity of a 20 mL burette during titration. Table 4 below shows the results for testing the effect of additives with Resin 1 on ammonia gas release.

[0069] [Table 4]

[0070] The tube furnace results (Table 4) showed a significant reduction in ammonia gas emissions with the zeolite-containing samples. The formulation containing 10% zeolite showed a 21.3% (P-value: 0.0147) reduction in ammonia gas emissions compared to the control formulation. The formulation containing 10% limestone showed a 10.2% reduction (P-value: 0.156) compared to the control resin, also a significant result. These figures reflect a significant improvement as they relate to the reduction of ammonia emissions during curing.

[0071] The data was normalized to the amount of resin and hexamine in each preparation to account for the dilution effect by using the amount of ammonia produced and dividing only by the amount of resin and hexamine in each sample (instead of the total sample weight). The normalized results more accurately reflect the amount of ammonia sorbed by each additive. The preparation containing 10% zeolite showed a 12.5% ​​reduction in ammonia emissions relative to the control resin, while the 10% limestone preparation showed a 0.20% reduction. This result demonstrates the important advantage of porous inorganic zeolites through their ability to sorb significantly greater amounts of ammonia compared to the negligible ammonia sorption on non-porous inorganic fillers.

[0072] A second tube furnace data set was generated using Novolac 1 resin, but here the hexamine concentration of both the control preparation and the zeolite-containing material was held constant. Table 5 below summarizes the resin preparations and results.

[0073] [Table 5]

[0074] When the samples had comparable hexamine concentrations, a 13.3% reduction in ammonia gas release was observed (P = 0.02), which was comparable to the normalized gas release reduction (12.5%) reported in Table 4. These values ​​represent the total amount of ammonia trapped by the clinoptilolite zeolite.

[0075] In summary, the presence of clinoptilolite zeolite in the novolac-hexamine preparation resulted in a significant reduction in the ammonia produced, by more than 21%.

[0076] Reduce sticking and contamination To test for resin sticking and staining (wood flour composites), wood flour was first dried in a forced air oven at 125°C for 3 hours. After cooling, the wood flour was combined with the novolac resin powder in a can and placed in a roller mill with stirring balls for at least 30 minutes to mix the wood flour uniformly with the compounded resin. An aluminum Q-plate preheated to 180°C was used in a hydraulic press. At least 1g of the resin / wood mixture was placed in the mold on the lower plate and tapped until the mixture was uniform. The upper top plate was used to sandwich the resin / wood mixture. The plates were pressed together using a hydraulic press at 180°C. The press was opened and the top plate was lightly tapped to determine if it moved freely. If the plates moved freely, the plate sample was given a score of 0 for sticking. If the plates stuck together, the sample was given a score of 1 for sticking. The above process was repeated 20 times with the same plates to observe the remaining stain for visual evaluation and to give a % score for sticking.

[0077] The sticking and staining tests were completed using a heated press and aluminum Q-plates. Figure 2 shows the visual staining on the Q-plates after the press cycle. Top row: 2854-1-1, 2854-1-2-1 and 2854-1-3-1. Bottom row: 2854-1-4-1, 2854-1-5-1 and 2854-1-6-1. The "B" on each plate indicates the lower plate used for the test evaluation for staining. In this study, it was observed that the control had significantly more sticking and staining than any of the preparations containing clinoptilolite zeolite. Table 6 below summarizes the staining test results. Sample 2854-1-5-1 produced the best results by minimizing both sticking and staining. This is advantageous for reducing cleaning, downtime and reducing scrap in wood forming operations.

[0078] [Table 6]

[0079] Reduced odor of cured articles Odor observations were performed by four observers, one blinded to sample composition. Observations were made on cured TGA samples (prior to grinding for TGA testing). Observations were made that are consistent with the hypothesized sorption effect of ammonia into porous clinoptilolite, which is favorable for the manufacture and use of the composite.

[0080] [Table 7]

[0081] Comparison of resin properties between control and modified resin formulations: The effect of varying the composition of the powdered resin formulation on the manufacturing process and on the final physical properties was evaluated to determine the negative impact caused by the sorbent. Table 8 shows the rheological properties as indicated by glass plate flow (mm) for the powder formulations tested at 125°C.

[0082] [Table 8]

[0083] Rheology was measured as a function of glass plate flow. Glass plate flow was measured using a forced air oven with an external crankshaft to raise and lower the shelf at 60°. A handheld pill press was used to press 0.50 g of the powder mixture into pellets with a diameter of 12.5 ± 3 mm and a thickness of 4.8 ± 0.2 mm. The resin pellets were then placed on a glass slide and on a wire mesh tray. The tray was placed in a 125° oven for 3 minutes, then the shelf was lowered to 60° for an additional 15 minutes, after which the shelf was returned to its original horizontal position and the wire mesh tray was removed. The pellet and flow were measured by the rear of the pellet to the very end of the flow (this length includes the pellet diameter).

[0084] Glass plate flow is often affected by inorganic components by shortening the flow, as is the case with the slight shortening of flow (3mm) when clinoptilolite zeolite is added at 10%. This can be beneficial in processing, as resins with longer flows tend to show resin spots on the finished part.

[0085] Comparison of properties between control and modified resin (cured resin properties) To produce resin-only plaques: Three resin samples (2854-6-1, 2854-6-2, and 2854-6-3) were first B-staged (i.e., partially cured) for 3 minutes on a foil-lined pan in a vacuum oven set at 160°C and 27" vacuum, after which the oven was opened and the samples were rotated 180° to ensure uniform B-staging, and the process was repeated for an additional 3 minutes. The B-staged resin was then crushed and 70g was then evenly spread into a mold to obtain a 6"x4"x1.5" "plaque" for testing. A large aluminum bar was placed on the top surface of the mold. The mold was then placed into a plastic heat-resistant bag and 3mm phenolic shims were placed on the ends of the mold to ensure proper thickness of the molded piece. The bag was then sealed with vacuum tape. The bagged mold was pressed in a preheated hydraulic press at 160°C and 27" vacuum. The press force was ramped from 0 to 20 tons over the course of 10 minutes and then held at 20 tons for 50 minutes. This process resulted in plaques that were subsequently cut to specified sizes for DMA and 3-point bend testing as reported in Tables 9 and 10 below.

[0086] [Table 9]

[0087] As can be seen in Table 9, the DMA results from the clinoptilolite-containing material (2854-6-2) and the control (2854-6-1) are particularly g were almost identical.

[0088] [Table 10]

[0089] Our results show an increase in the elastic modulus at 10% content in formulation 2854-6-2 for three-point bending tests with clinoptilolite zeolite. This is beneficial in composite formulations that require or benefit from additional stiffness. Three-point bending tests were performed according to ASTM D790-03.

[0090] TGA results To prepare samples for TGA testing: 2g of the resin sample was placed into a 1" diameter circular mold and pressed with 10 tons of force for 20 seconds to form a pellet. The pellet was then wrapped in foil and placed between two 12"'12" steel plates. The steel plates with the pellet were then placed in an oven and a metal weight was placed on top of the sample. The oven was then heated to 175°C and maintained at 175°C for 5-18 hours. After this curing period, the sample was removed and allowed to cool.

[0091] The cured resin was ground using a mini mill in short 2-3 second bursts to obtain a coarse grind. The sample was sieved through #12 and #20 sieves. The sample used for testing was retained on the #20 sieve. 20-25 mg of sample was loaded into the TGA instrument.

[0092] Thermogravimetric analysis (TGA) A 20-25 mg sample prepared for thermogravimetric analysis was loaded into a pre-weighed aluminum pan in a TA Instruments Q50 thermogravimetric analyzer. The temperature was then ramped from ambient to 1000 °C under nitrogen atmosphere. The temperatures at 5% and 10% weight loss were used to characterize the onset of decomposition, and the degree of the peak of the % weight derivative curve was used as the peak decomposition temperature. The peak decomposition temperature is measured from the peak temperature of the derivative of the weight % curve. The % mass remaining at 1000 °C was characterized as the % char yield. The percent char at 1000 °C is a measure of the ability of the material to produce carbon with a higher char level at 1000 °C and is generally accepted as providing a beneficial property for high temperature stability.

[0093] [Table 11]

[0094] The results from thermogravimetric analysis (TGA) are collated with typical measurements for a phenolic novolac resin with inorganic components.

[0095] Application testing: Incorporation of clinoptilolite into wood composites To obtain the wood composite bars: The wood flour was first dried in a forced air oven at 125°C for 3 hours. After cooling, the wood flour was combined with the novolac resin powder in a can and placed in a roller mill and agitated with a ball for at least 30 minutes. After mixing, 30g of the resin-wood flour mixture was placed in a mold preheated to 180°C with a preheated stainless steel press bar at the bottom. The powder was spread evenly in the mold and the mold was placed in a preheated 180°C hydraulic press immediately after the preheated stainless steel top bar was placed in place. After pressing, the mold was removed and the metal press bar was removed to extract the final molded wood composite bar. This method produced wood composite bars for testing, which were 1.125" wide x 4.0" long and approximately 0.5" to 0.75" thick.

[0096] [Table 12]

[0097] Samples 2846-139-control, 2846-139-A1, and 2846-A2 were prepared and pressed to maintain a constant pressure, while later samples (2854-1-1 control, 2854-1-3, and 2854-1-5) were set at an initial pressure and the gap between the plates was held constant for the duration of the press. Data entries 4 through 6 showed minimal variation.

[0098] [Table 13]

[0099] Two different wood preparations were used for the evaluation. 2846-139-The control preparation performed better than the other two preparations, but the amount of error in the measurements was large. To obtain more realistic measurements, the latter preparation was used in the application preparation, and the measurements obtained had much less deviation per sample. The preparation containing 10% clinoptilolite zeolite performed better than or equal to the control under these more realistic conditions.

[0100] The water absorption of the bars was comparable to each other, i.e., a baseline measurement that is sought to be minimized for applications by a typical wood molding customer. The wood bars were prepared for water absorption as described above for TGA testing. The prepared wood bars were cut in half against the grain direction with a band saw. The blocks were weighed and then submerged in room temperature deionized water for 24 hours. After soaking, each piece was removed from the water and gently wiped with tissue paper to remove surface water, then weighed to obtain the percent water absorption. Table 14 summarizes these results.

[0101] [Table 14]

[0102] In other particular embodiments, the cured resin compositions containing a phenolic-aldehyde resin, hexamine and a sorbent described herein can include any combination of the following properties: (a) a glass plate flow of 10 mm to 200 mm at 125° C., as measured by the test procedures described herein; the glass plate flow may also range from a minimum of about 10 mm, about 15 mm, or about 20 mm, to a maximum of about 140 mm, about 160 mm, or about 180 mm; the glass plate flow may also range from a minimum of about 10 mm, about 15 mm, or about 20 mm, to a maximum of about 60 mm, about 75 mm, or about 100 mm; (b) a modulus of rupture (MOR) of about 40 to about 150 MPa, as measured by ASTM D790-03; the MOR may also range from a low of about 40, about 45, or about 50, to a high of about 100, about 130, or about 140 MPa; (c) a maximum bending stress (modulus of elasticity) of about 5.0 to 8.0 GPa, as measured by ASTM D790; the MOE may also range from a low of about 5.0, about 5.5, or about 6.0, to a high of about 7.0, about 7.5, or about 7.8 GPa; and / or (d) Char residue percentage, as measured by thermogravimetric analysis (TGA), is about 30 to about 75% at 1,000°C in nitrogen and about 0 to about 30% at 550°C in air.

[0103] In other specific embodiments, the wood composite made from the hardened phenolic-aldehyde resin, hexamine and a sorbent described herein and mixed with a plurality of wood particles can include any combination of the following properties: (a) a water absorption rate of about 5 to 45% by weight after 24 hours of immersion; the water absorption rate may also range from a low of about 5, about 10, or about 12% by weight to a high of about 30, about 40, or about 44% by weight; (b) a modulus of elasticity (MOE) of about 800 to 2000 MPa; the MOE may also range from a low of about 850, about 950, or about 1,100 MPa to a high of about 1400, about 1600, or about 1950 MPa; and / or (c) a maximum bending stress of about 25 to about 70 MPa; the maximum bending stress may also range from a low of about 30, about 35, or about 40, to a high of about 55, about 60, or about 65 MPa.

[0104] In one or more other embodiments, methods are provided for making the cured resins described herein. One particular method includes:

[0105] Certain embodiments and features are described using a set of upper numerical limits and a set of lower numerical limits. It is understood that ranges including combinations of any two values, such as combinations of any lower limit with any upper limit, combinations of any two lower limits, and / or combinations of any two upper limits, are contemplated unless otherwise stated. Certain lower limits, upper limits, and ranges appear in one or more claims below. All numerical values ​​are "about" or "approximately" indicated values, taking into account experimental error and variations that would be expected by one of ordinary skill in the art.

[0106] Various terms are defined above. To the extent that a term used in the claims is not defined above, it should be given the broadest definition that one of ordinary skill in the art would have given that term as reflected in at least one published publication or issued patent. Furthermore, all patents, test procedures, and other documents cited in this application are incorporated by reference in their entirety (to the extent such disclosure is not inconsistent with this application and for all jurisdictions in which such incorporation is permitted).

[0107] While the forgoing is directed to embodiments of the present invention, other and further embodiments of the invention may be devised without departing from the basic scope thereof, which scope is determined by the following claims.

Claims

1. A binder composition comprising 50 to 93 weight percent of a phenolic-aldehyde novolac resin, 5 to 15 weight percent of hexamine, and 2 to 30 weight percent of at least one sorbent, based on the total weight of the resin.

2. 2. The binder composition of claim 1, wherein said phenolic-aldehyde novolac resin has a molar ratio of formaldehyde of about 0.2:1 to about 0.7:

1.

3. 2. The binder composition of claim 1, wherein said phenolic-aldehyde novolac resin has a molar ratio of formaldehyde to phenolic of about 0.5:1 to about 0.95:

1.

4. The binder composition of claim 1 which is a powder.

5. 10. The binder composition of claim 1, wherein the sorbent is a porous inorganic material having a pore size of 2 Å to 20 Å configured to trap ammonia gas.

6. 2. The binder composition of claim 1, wherein the sorbent is a clinoptilolite zeolite.

7. 2. The binder composition of claim 1, wherein the weight ratio of said sorbent to said hexamine is about 1:0.

5.

8. 1. A cured resin composition comprising 50 to 93 weight percent of a phenolic-aldehyde novolac resin, 5 to 15 weight percent of hexamine, and 2 to 30 weight percent of at least one sorbent, based on the total weight of the resin composition; The cured resin composition has a glass plate flow of 10 mm to 200 mm at 125° C., a modulus of rupture (MOR) of about 40 to about 150 MPa as measured by ASTM D790-03, a maximum flexural stress (elastic modulus) of about 5.0 to 8.0 GPa, and a % char residue of about 30 to about 75% at 1,000° C. in nitrogen as measured by thermogravimetric analysis (TGA).

9. 9. The cured resin composition of claim 8, wherein the sorbent is a porous inorganic material having a pore size of 2 Å to 20 Å, and the weight ratio of the sorbent to the hexamine is about 1:0.

5.

10. 10. The cured resin composition of claim 9, wherein the sorbent is a clinoptilolite zeolite.

11. 10. The cured resin composition of claim 9, wherein the sorbent is clinoptilolite zeolite and is 10% by weight of the total weight of the binder composition.

12. 9. The cured resin composition of claim 8, which is only partially cured at a temperature of from about 70° C. to about 250° C. for from about 5 seconds to about 150 seconds.

13. A wood composite made from the hardened binder composition of claim 9.

14. The wood composite of claim 13 having a water absorption of about 5 to 45% by weight after 24 hours of immersion.

15. 14. The wood composite of claim 13 having a modulus of elasticity (MOE) of about 800 to 2000 MPa and a maximum bending stress of about 25 to about 70 MPa.